El Partido Comunista de Chile: antecedentes ideológicos de su estrategia hacia la Unidad Popular (1961-1970) - Venegas Valdebenito, Hernán (Revista de Historia Social y de las Mentalidades, 2025)
This research concentrates in the history of the ideological and pragmatic propositions that the Chilean Communist Party developed in order to establish wider social and political alliances. The Communist Party assumed the thesis of the «pacific way»as a mode to reach socialism within a democratic expansion. This work also study the party’s proposals during the 60’, its initiatives to build the Unidad Popular and its major political definitions to begin the socialism’s way.